MANAGING LECTURERS’ PERFORMANCE BY USING STUDENT SATISFACTION SURVEY - Muizzudin, Muizzudin (Idaarah: Jurnal Manajemen Pendidikan, 2022)
Lecturers play a very significant role in education. Managing their performance can give good impacts to the quality of teaching processes and outcomes. There are actually many approaches to manage their performance. One of the approaches worth considering is students’ feedback combined with the marketing concept of ‘customer satisfaction’ since students can be considered customers. The concept of student satisfaction is too broad. It ranges from facilities to lecturers. This paper focuses only on managing the lecturer’s performance based on student satisfaction towards what normally a lecturer has done in teaching and learning. The data is collected from the questionnaire provided for the students. The research is expected to map the weakness and strength areas of the lecturer in four classifications: first, what the lecturer should improve because the lecturer’s performance perceived by the students is in the low level and the students’ expectation is in the high level; second, what the lecturer should maintain or keep going because the lecturer’s performance and the students’ expectation at the same time are in the high level; third, what the lecturer should maintain but think about the weighting of it because the lecturer’s performance is in the low level and the students’ expectation is also in the low level; fourth, what the lecturer should reduce the emphasis if possible because the lecturer’s performance is in the high level and the students’ expectation is in the low level. The result shows that with the four classifications the lecturer’s performance can be managed well. Consequently, the lecturer can do the planned evaluation action to improve the performance accordingly in measurable and manageable way.